Coumarin derivatives against amyloid-beta 40 – 42 peptide andtauprotein - Kowalczyk, Joanna; Skalicka-Wozniak, Krystyna; Budzynska, Barbara; Sayed, Nesrine El; Espargaró, Alba; Sabate, Raimon (Current Issues in Pharmacy and Medical Sciences, 2022)
In preclinical studies, simple coumarins (scoparone, limettin) and furanocoumarins (imperatorin, xanthotoxin, bergapten) have already found to demonstrate procognitive abilities. This suggests that they hold antioxidative, anti-inflammatory and inhibitory action towards acetylcholinesterase activities. However, little is known about their influence on the amyloidal structure formation, the leading cause of Alzheimer’s disease (AD).In vitroandin celluloassays were applied to evaluate the effect of selected coumarins on the different stages of Aβ40/42 andtauprotein aggregation. Kinetic analyses were performed to evaluate their inhibiting abilities in time. Limettin revealed the most potent inhibiting profile towards Aβ40 aggregation, however, all tested compounds presented low influence on Aβ42 and tau protein aggregation inhibition. Despite the preliminary stage of the project, the promising effects of coumarins on Aβ40 aggregation were shown. This suggests the coumarin scaffold can serve as a potential multitarget agent in AD treatment, but further studies are required to confirm this.